2022
DOI: 10.1186/s12913-022-07907-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-design and evaluation of a patient-centred transition programme for stroke patients, combining case management and access to an internet information platform: study protocol for a randomized controlled trial - NAVISTROKE

Abstract: Background Stroke affects many aspects of life in stroke survivors and their family, and returning home after hospital discharge is a key step for the patient and his or her relatives. Patients and caregivers report a significant need for advice and information during this transition period. Our hypothesis is that, through a comprehensive, individualised and flexible support for patients and their caregivers, a patient-centred post-stroke hospital/home transition programme, combining an Interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Improving both clinical management and research can be done through the implementation of a clinical research mentorship program ( 43 ). The development of these new mHealth technologies and solutions, allowing for continuous patient monitoring and follow-up ( 44 , 45 ), is also a unique opportunity to develop more individualized rehabilitation ( 46 48 ). According to the WHO, people-centered care is a much broader concept than only actively involving the patient in the care.…”
Section: Call For Actionmentioning
confidence: 99%
“…Improving both clinical management and research can be done through the implementation of a clinical research mentorship program ( 43 ). The development of these new mHealth technologies and solutions, allowing for continuous patient monitoring and follow-up ( 44 , 45 ), is also a unique opportunity to develop more individualized rehabilitation ( 46 48 ). According to the WHO, people-centered care is a much broader concept than only actively involving the patient in the care.…”
Section: Call For Actionmentioning
confidence: 99%
“…At the organization level, researchers indicated that co-design could help them generate solutions grounded in the context, increasing organizational innovation capacity [ 32 , 35 ]. Researchers also used co-design methods because these were successfully used to produce practical, accessible, and sustainable interventions and improve services in other healthcare settings (e.g., [ 49 , 50 , 62 , 72 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Most data sources (n = 73/89, 82%) conducted co-design with multiple participant types (e.g., individuals with stroke, stroke family members/caregivers, stroke clinicians). Of the included data sources, nearly all (n = 87/89, 98%) involved people with stroke, and some specifically targeted individuals with aphasia (e.g., [ 43 , 46 , 57 , 65 , 67 , 92 , 94 ]), with a loss of visual field (e.g., [ 70 ]), current or former hospital inpatients (e.g., [ 32 , 45 , 49 , 50 , 66 , 79 , 86 , 87 ]), with cognitive and/or physical impairments (e.g., [ 85 ]), with certain levels of physical or functional impairments (e.g., “severe upper-limb deficits” [ 91 ] and “mild to moderate level of disability” [ 55 ]), First Nations community members with stroke [ 64 ] and Aboriginal and/or Torres Strait Islander Peoples with stroke [ 43 ]. A few researchers specified that cognitive ability was determined through clinical judgement and/or based on whether an individual could provide informed consent and participate in the study activities [ 74 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the development of new affordable and portable technology and solutions can enable continuous patient monitoring and follow-up ( 51 , 52 ), leading to more individualized rehabilitation ( 53 ) and could allow the validation of new interventions or technologies ( 54 ). People-centered care is essential for this, as it involves actively involving the patient in the care, providing them with the knowledge and support they need to make decisions and engage in their own care, and ensuring that caregivers are performing optimally within a supportive working environment ( 55 ).…”
Section: Conclusion and Call To Actionmentioning
confidence: 99%